Big Five Personality sebagai Prediktor Kreativitas dalam Meningkatkan Kinerja Angggota Dewan - Hardani Widhiastuti (Faculty of Psychology, Universitas Gadjah Mada, 2014)
This study aimed to analyze the influence of the Big Five Personality Factors, which consists of Neuroticism, Extraversion, Openness to Experience, Agreeableness and Conscientiousness on the Creativity and its implications to the performance of City Council members of ‘S’ city within the period of 2009-2014. A total number of 36 legistators who were still active became the subjects of the research. Linear Regression Analysis of the two phases was used to analyze the collected data with SPSS 19. The results showed that for Extraversion, t valued 2,340 with sig. 0.026, for Agreeableness, t valued 2.760 with sig. 0,010 and for Conscientiousness, t valued 2,241 with sig. 0,033. Thus, all the three factors had significant and positive effect on creativity. In the two-stage regression test, the value of t was 2.431 with a sig. 0,020. In general, the Big Five Personality traits have made positive and significant effect on the creativity and performance of City Council members of the ‘S’ city. Keywords: Big Five Personality, creativity, performance, council